"Rooted" Freedom, "Deep Respect": Living a Life Worthy of Dignity as a Muslim Woman in the Netherlands. Issue 2 (3rd April 2022) - Pool, Fernande W.
ABSTRACT: This research reveals perspectives on and experiences of human flourishing amongst devout Muslim women with an immigrant background in the Netherlands. The aim is to assess what this tells us about worthwhile development generally in a multi-cultural Western country, while drawing comparisons with previous research in India. Following Nussbaum's capabilities approach, I asked 39 women: what are the basic requirements for a life worthy of dignity? Freedom and respect stood out on their lists of essential requirements. I explore the meaning and content of freedom and respect as conveyed by the women. The kind of freedom they intend is foremost freedom of religion, which is at once broader and narrower than religious freedom as constitutionally enshrined. Broader, because it is an all-encompassing freedom to live by a system of meaning. Narrower, because it refers to a relational, "rooted" freedom. Yet even where religious freedom is institutionally guaranteed, everyday encounters between citizens can crucially impact on the experience of dignity. Therefore, the second essential element is respect. The kind of respect necessary for a life worthy of dignity is not a superficial toleration but "deep respect." Finally, I explore the possible difficulties in a liberal society for securing "deep respect".